Synthesis and sintering impact on the properties of willemite based glass-ceramics using rice husk waste as silica source - Wahab, R. A. A.; Zaid, M. H. M.; Matori, Khamirul Amin; Halimah, M. K.; Sidek, H. A. A.; Fen, Y. W.; Abdu, A.; Shofri, M. F. M.; Jaafar, S. H. (International Institute for the Science of Sintering, 2022)
The impact of sintering duration on willemite-based glass-ceramics (WGC) derived from the ZnO-B2O3-SiO2 host system through a conventional melt-quenching method by incorporating rice husk ash (RHA) as the silica (SiO2) source was comprehensively studied by means of physical, structural, and optical properties. The increment of sintering duration elevated the diffusivity rate resulting in a gradual increment of bulk density and linear shrinkage over sintering time. The XRD patterns affirmed the β-Zn2SiO4 phase formed after sintering at 700oC for 2 h, followed by α-Zn2SiO4 crystallization at a higher holding time. FESEM observation revealed that Zn2SiO4 embedded in the glassy solid phase and grew in equiaxed shape crystals as the holding time increased. Absorption spectra revealed the increasing trend in absorption bands with an increase in sintering duration due to the intensification of Zn2SiO4 crystallization thus escalating the green emission. Thus, this WGC will be applied as optically phosphor materials.